Impact of Gender on the Association of Epicardial Fat Thickness, Obesity, and Circadian Blood Pressure Pattern in Hypertensive Patients - In Kyoung Shim; Kyoung-Im Cho; Hyun-Su Kim; Jung-Ho Heo; Tae Joon Cha (Journal of Diabetes Research)
This study aimed to investigate the effects of gender on the association between epicardial fat thickness (EFT) and circadian blood pressure (BP) changes in patients with recently diagnosed essential hypertension (EH). A total of 441 patients with EH (male/female: 236/205, mean age: 50.7 ± 13.8) and 83 control patients underwent 24-hour ambulatory BP monitoring and echocardiography. Obese EH patients had higher circadian BP profile with BP variability, wall thickness, and left ventricular mass than nonobese EH patients and controls (all p’s <0.05) without gender differences. EFT was higher in female than in male patients (7.0 ± 2.5 versus 5.9 ± 2.2 mm, p<0.001) and higher in the obese female EH group (7.5 ± 2.6 mm) than in the control (6.4 ± 2.8 mm) or nonobese EH group (6.7 ± 2.8 mm) among women, whereas EFT did not vary among males (5.9 ± 1.9 versus 6.0 ± 2.7 versus 5.9 ± 2.4 mm, p=0.937). Multivariate logistic regression analysis demonstrated that the 24-hour mean BP variability was associated with SBP (p=0.018) and EFT (p=0.016) in female patients, but not in male patients. The relationships among circadian BP variability, obesity, and EFT were affected by gender in different manners. EFT may be a more valuable parameter in the evaluation of BP severity and obesity in women than in men.